Strategi Komunikasi dalam Memelihara Kualitas Hubungan Long Distance Marriage: Studi Literatur Review - Nabila Fadillah Fitriani; Rahma Fauziah; Alif Daffa Razyansah; Fadhatul al Hatta; Eky Indra Pratama; Rahmadianti Aulia (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
The phenomenon of Long Distance Marriage (LDM) has become increasingly prevalent in modern society due to occupational demands, educational pursuits, and geographical mobility. Effective communication plays a central role in maintaining the quality of marital relationships among LDM couples. This study aims to examine communication strategies used by LDM couples to sustain relationship quality through a Systematic Literature Review (SLR) using the PRISMA 2020 framework. A systematic search was conducted across five databases ResearchGate, Google Scholar, ScienceDirect, SAGE Journals, and SpringerLink, covering publications from 2017 to 2026. From an initial pool of 97 articles, 12 studies met the inclusion criteria and were synthesized. The findings reveal that the most dominant strategies include open interpersonal communication, consistent digital communication via platforms such as WhatsApp, video call, and voice call, conflict management, and the cultivation of trust and commitment. Communication quality was found to be more influential than communication frequency in sustaining emotional closeness. Additionally, spirituality and emotional regulation emerged as significant supporting factors. These strategies positively impact marital satisfaction, commitment, emotional closeness, and resilience among LDM couples. These findings underscore the critical role of communication in preserving marital quality across geographical distance.